2016
DOI: 10.17759/sps.2016070408
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Virtual Commmunication Training for Psychological Support to Unemployed: Randomized Controlled Trial

Abstract: Practice in job interview skills is an important step toward successful employment of unemployed. The purpose of the study was to assess the effectiveness of the virtual communicative training developed by us in interviewing skills training of the unemployed with the employer. Participants were randomized into control (n=16) and experimental (n=18) con- ditions. We have created software “Virtual Recruiter” that provides an experience with which job seekers can systematically improve their job interview skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A self-report method was used to assess psychological readiness for job interviewing. We have revised the Psychological Willingness to a Job Interview Questionnaire that we used in our previous study ( Aysina, 2016 ) and developed the Psychological Readiness for Job Interviewing Scale, which included a set of seven items (see Appendix ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A self-report method was used to assess psychological readiness for job interviewing. We have revised the Psychological Willingness to a Job Interview Questionnaire that we used in our previous study ( Aysina, 2016 ) and developed the Psychological Readiness for Job Interviewing Scale, which included a set of seven items (see Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the present study was to assess the efficacy of a computer simulation - Job Interview Simulation Training (JIST) - in preparing healthy unemployed individuals of pre-retirement age for job interviewing. We have already tested JIST on a sample of job seekers of different ages, including short-term and long-term unemployed persons, as well as on a small group of the long-term unemployed ( Aysina, 2016 ; Aysina, Maksimenko, & Nikiforov, 2016 ). Our findings demonstrated that the training system could enhance psychological willingness to go through a job interview in different categories of the unemployed ( Aysina, 2016 ) and improve job interview performance and job interview self-confidence in individuals who had been jobless for 12 months or longer ( Aysina et al, 2016 ).…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the socio-economic inclusion of NEET youth in public life should be carried out comprehensively at multiple different levels, including personal, educational, and labor. A number of studies have shown that individual training can achieve a fragmentary effect in the form of increased labor motivation (Ushakova 2021;Aysina 2016;Selezneva 2008). However, for a systemic solution to the problem, state regulation measures are necessary.…”
Section: Inequality In Non-cognitive Skills Of Russian Youth Dependin...mentioning
confidence: 99%